Glycemic Status of Type 2 Diabetic Subjects On Different Anti-Diabetic Management - Samdani, Tasrina Shamnaz; Rahim, Muhammad Abdur; Mitra, Palash; Ahmed, AKM Shaheen; Uddin, Khwaja Nazim (BIRDEM Medical Journal, 2017)
Background: Diabetes mellitus (DM) is a complex multi-system disorder that may lead to diabetes specific complications and target organ damage which can be prevented or delayed by good or strict glycemic control. Our aims were to evaluate the glycemic status of adult type 2 DM (T2DM) patients on different anti-diabetic management, to evaluate role of education and economic status on glycemic control and to correlate glycemic status with complications. Methods: This cross-sectional study was conducted in BIRDEM General Hospital from November 2013 to April 2015. Data were collected in a pre-formed data collection form, purposively and consecutively from 300 T2DM patients who were diagnosed as diabetic for 3 months or more and were compliant, after face to face interview and undergoing the required physical examinations. Then data were compiled and analyzed accordingly. Result: Neither the educational level nor the monthly income had any influence on glycemic control. Only 17% of the patients had good glycemic control (HbA1c <7) in spite of different anti-DM managements. The overall mean HbA1C was 8.9±1.9%, among which the group of patients with medical nutrition therapy had the lowest mean HbA1c level (8.5±1.3%). Chronic kidney disease and polyneuropathy are the two commonest (45% and 40% respectively) complications with a significant (r=1, p=0.000) positive correlation between both macro and microvascular complications of DM with uncontrolled glycemic status. Conclusion: From the current study it can be concluded that glycemic control is rarely achieved and no treatment regimen is superior to other in achieving glycemic control. Patients educational or income level did not have any influence in glycemic control and there is a strong positive correlation between uncontrolled T2DM and its complications. Birdem Med J 2017; 7(2): 121-126